Discovery of Human-Specific Immunodominant Chlamydia trachomatis B Cell Epitopes - K. Shamsur Rahman (American Society for Microbiology, 2018)
ABSTRACT Chlamydia species-specific serology is compromised by cross-reactivity of the gold standard microimmunofluorescence (MIF) or commercial enzyme-linked immunosorbent assays (ELISAs). This study was conducted to discover novel C. trachomatis-specific peptide antigens that were recognized only by the antibody response of the natural human host. We evaluated a library of 271 peptide antigens from immunodominant C. trachomatis proteins by reactivity with 125 C. trachomatis antibody-positive sera from women with PCR-confirmed C. trachomatis infection and 17 C. trachomatis antibody-negative sera from low-risk women never diagnosed with C. trachomatis infection. These C. trachomatis peptide antigens had been predicted in silico to contain B cell epitopes but had been nonreactive with mouse hyperimmune sera against C. trachomatis. We discovered 38 novel human host-dependent antigens from 20 immunodominant C. trachomatis proteins (PmpD, IncE, IncG, CT529, CT618, CT442, TarP, CT143, CT813, CT795, CT223, PmpC, CT875, CT579, LcrE, IncA, CT226, CT694, Hsp60, and pGP3). Using these human sera, we also confirmed 10 C. trachomatis B cell epitopes from 6 immunodominant C. trachomatis proteins (OmpA, PmpD, IncE, IncG, CT529, and CT618) as host species-independent epitopes that had been previously identified by their reactivity with mouse hyperimmune sera against C. trachomatis. ELISA reactivities against these peptides correlated strongly with the C. trachomatis microimmunofluorescence (MIF) text results (Pearson’s correlation coefficient [R] = 0.80; P < 10−6). These C. trachomatis peptide antigens do not cross-react with antibodies against other Chlamydia species and are therefore suitable for species-specific detection of antibodies against C. trachomatis. This study identified an extended set of peptide antigens for simple C. trachomatis-specific ELISA serology. IMPORTANCE Current serological assays for species-specific detection of anti-Chlamydia species antibodies suffer from well-known shortcomings in specificity and ease of use. Due to the high prevalences of both anti-C. trachomatis and anti-C. pneumoniae antibodies in human populations, species-specific serology is unreliable. Therefore, novel specific and simple assays for chlamydial serology are urgently needed. Conventional antigens are problematic due to extensive cross-reactivity within Chlamydia spp. Using accurate B cell epitope prediction and a robust peptide ELISA methodology developed in our laboratory, we identified immunodominant C. trachomatis B cell epitopes by screening performed with sera from C. trachomatis-infected women. We discovered 38 novel human host-dependent antigens from 20 immunodominant C. trachomatis proteins, in addition to confirming 10 host-independent mouse serum peptide antigens that had been identified previously. This extended set of highly specific C. trachomatis peptide antigens can be used in simple ELISA or multiplexed microarray formats and will provide high specificity and sensitivity to human C. trachomatis serodiagnosis.